"But it is our duty!" Exploring Gazprom's reluctance to Russian gas sector reform. Issue 1 (2nd January 2019) - Loe, Julia S. P.
ABSTRACT: Reform of the Russian domestic natural gas sector has been discussed for several decades but has not been carried out. The state-controlled energy company Gazprom holds a dominant position in the domestic market, supplying the population with gas, carrying out societal functions, and in return getting privileges from the state. Recently, however, independent gas producers have increased their market shares and are lobbying for liberalization. While Gazprom might gain from reform, it continues to warn against the dangers of altering the gas market structure too abruptly. Analyzing Gazprom's reasoning through an ideational analytical lens, this article finds that Gazprom's reluctance to change can be explained not only by its interests but also by norms and beliefs. Reform studies should take note of Gazprom's idea of "keeping the country together, " not least because the company has a sounding board in the President, who makes the final decisions.